Exploring The Pathological Changes AssociatedWith Acute And Chronic Rejection In Organ Transplants (Journal of Pharmaceutical Negative Results, 2022)
Background : Transplantation is a decisive treatment method for end-stage organ dysfunction, but it has its problems because of the immune system. Currently the main scholarship directs onto the pathological alterations in acute and chronic rejection which are the main causes of graft failure. Objectives : To explore the general morphological changes that occur following acute and chronic rejection in organ transplants with special emphasis on immune and inflammation markers and tissue damage. Study design: A Cross Sectional Study.Place and duration of study. Department of Pathology Watim medical and dental college, rawat from July 2021 to Dec 2021Methods : A cross sectional study was done on 150 transplant patients who all went through a renal biopsy where we looked at samples of immune response, tissue injury and fibrosis. Hence, sanctions of standard deviation and p-value were made to determine the probability of acute and chronic rejections. Furthermore, assessment was also made on the association of immune biomarkers to the extent of tissue pathology. Results: From 150 patients there were observed 60 demonstrated acute rejection and 90 patients with chronic rejection. The increase of mean tissue damage scores between the two groups was found to be significant (< 0. 05, SD = 5. 2 acute rejection, SD = 7. 8 chronic rejection). Chronic rejection was higher fibrosis and compared to acute rejection, there was inflammation. Conclusion : This is the first report on acute and chronic rejection assocated with specific histological changes in organ transplants. Knowledge of such differences enhances post-transplant care and results in development of unique interventions that would minimize the incidences of graft failure.